Genomic and immunocyte characterisation of bloodstream infection caused by Klebsiella pneumoniae - Wei Yu; Chen Huang; Xiang Lian; Lushun Jinag; Hong Li; Ping Shen; Yonghong Xiao (BMC, 2024)
Abstract Objectives The aim of this study was to evaluate the characteristics of immunocyte associated with bloodstream infection (BSI) caused by Klebsiella pneumoniae (Kpn). Methods Patients with BSI-Kpn were included from 2015 to 2022 in our hospital. Immunocyte subpopulations of enrolled BSI-Kpn patients were tested on the same day of blood culture using multicolor flow cytometry analysis. Antibiotic susceptibility test was determined by agar dilution or broth dilution method. All included isolates were subjected to whole genome sequencing and comparative genomics analysis. Clinical and genetic data were integrated to investigate the risk factors associated with clinical outcome. Results There were 173 patients with non-duplicate BSI-Kpn, including 81 carbapenem-resistant Kpn (CRKP), 30 extended-spectrum β-lactamases producing Kpn (ESBL-Kpn), 62 none CRKP or ESBL-Kpn (S-Kpn). Among 68 ST11-CRKP isolates, ST11-O2v1:KL64 was the most common serotypes cluster (77.9%, 53/68), followed by ST11-OL101: KL47 (13.2%, 9/68). Compared with CSKP group, subpopulations of immunocyte in patients with CRKP were significantly lower (P < 0.01). In patients with ST11-O2v1:KL64 BSI-Kpn, the level of cytotoxic T lymphocytes (CD3 + CD8 +) is the highest, while the B lymphocytes (CD3-CD19 +) was the least. In addition, the level of immunocyte in patients with Kpn co-harbored clpV-ybtQ-qacE were lower than that in patients with Kpn harbored one of clpV, ybtQ or qacE and without these three genes. Furthermore, co-existence of clpV-ybtQ-qacE was independently associated with a higher risk for 30-day mortality. Conclusions The results demonstrate that patients with BSI-CRKP, especially for ST11-O2v1:KL64, exhibit lower leukomonocyte counts. In addition, BSI-Kpn co-harbored clpV-ybtQ-qacE is correlated to higher 30-day mortality.